Future trends of Finnish cement based construction - Marjalaakso, Mikko (My University, 2012)
The construction material sector, as a capital intensive industry, is highly vulnerable to rapid fluctuations in the economic cycles. In Finland this was witnessed especially during the late 2000s, as in 2007 and 2008 the demand for several construction materials exceeded their supply and right after this, in 2009 the demand collapsed fast as a result of an international recession. These factors brought about the need to study the future trends of the market place of the commissioning company, Finnsementti Oy. As reliable short term market forecasts for the sector are difficult to compose, the study concentrates primarily in examining and identifying the trends that are likely to affect the Finnish cement industry, and as an extension, the concrete industry in a frame of 10 to 15 years. The study’s scope comprehends also the examination of the domestic construction sector, as it represents the end user industry of both cement and concrete. These motives for the study produce the research problem, which is to conduct a trend analysis for cement based building in the Finnish market area in the 2020s. The theoretical frame for composing a trend analysis in the case of this study is twofold. This is due to the fact that both, the macro and micro environments of the examined industries are studied. The main methods used are the PESTE-model (macro) and Porter’s five forces model (micro). The study applies a qualitative approach and the data is gathered by interviewing a group of experts from the cement, concrete and construction industries. The result of the paper is an overall trend analysis for the Finnish cement based building sector, which is based on ‘sub trend analyses’ concerning four identified sub-sectors of the Finnish construction industry. The results are a combination of findings from these sub-sectors and the analyzed data that deals with the studied sector’s macro and micro environment. The conclusions provide an overall picture of the examined sectors’ potential future as a whole and by defined sub-sectors of the construction industry. The recognition of future trends in different areas of the construction industry can be applied as a means for an industry actor’s decision making and in estimating the types of construction that are likely to grow or decline. Finally, based on the analyzed data and conclusions, the commissioning company is provided with a brief SWOT analysis, that provides additional tools for decision making and planning processes regarding the future.